Resilience in J.S. Khairen’s Novel Dompet Ayah Sepatu Ibu: A Study of Max Weber’s Social Action - Khurun'in Rizki Az Zahra; Titik Indarti (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the form of resilience in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen using Max Weber’s social action theory. Resilience is understood as an individual’s ability to accept, face, and transform life’s problems through a process of adaptation and positive change. In Max Weber’s perspective, social action is defined as behavior oriented towards specific goals, whether driven by individual or collective interests. This theory encompasses four main concepts, namely instrumental rationality, value rationality, traditional rationality, and affective rationality. This study uses a qualitative descriptive method with a literary sociology approach. The data is sourced from the novel Dompet Ayah Sepatu Ibu (2023) in the form of quotations that represent the social action resilience of the characters in their efforts to break structural poverty. The data was collected through reading and note-taking techniques, then analyzed using objective hermeneutics. The results show that there are four types of resilience in Max Weber’s social actions, namely the resilience of instrumental rationality, the resilience of value rationality, the resilience of traditional actions, and the resilience of affective actions, which are causally interrelated. The conclusion of the study confirms that these four forms of action are the basis of the characters’ resilience in the novel.